Product Innovation Enhancement through Halal Food Certification: Evidence from Mondoretno MSMEs” - Eko Sariyekti; M. Abdul Munjid; Mohammed Hafiz Ali Wafa (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2026)
Halal food industry in Indonesia is growing rapidly, creating a significant opportunity for UMKM to develop halal product innovations. This innovation not only enhances product quality but also expands export opportunities, positioning Indonesia as a key player in the global halal industry. This study aims to analyze the role of halal certification in driving product innovation among UMKM in Mondoretno. The research employs a qualitative approach, with data collection methods including interviews, observations, and documentation, expected to provide direct data from the sources. The data analysis techniques involve data collection, reduction, and conclusion drawing from field findings, along with triangulation to ensure data validity. The research subjects are UMKM in Mondoretno operating in the halal food sector. The findings are expected to provide effective strategies for UMKM to enhance product innovation through halal certification. Halal certification not only increases consumer trust but also encourages UMKM to continuously innovate in creating high-quality products.